RIGHT TO PLAY - A NECESSITY (International Journal of Food and Nutritional Sciences, 2022)
It is really unfortunate that playing opportunity is being denied to children of developing countries due to mainly ill-conceived and badly implemented education policies on the one hand, and poverty, incongruent traditions and customs, etc. Too much stress on academic work, parental attitude, teachers’ apathy, indifference of the school administration, urbanization, mechanization of life routines, etc., seem to be adding fuel to the fire. In India as elsewhere, many children are seen becoming adults Without even having the chance of being on a playfield, entering a swimming pool or having a swing on the bar at least once in life. All this adversely affects the development of their personality on desirable lines. The television and mobile boom has pushed the child far into the abyss of inactivity, sloth and passivity -considered staunch emeies of natural growth and development.